Efectos de la realización de un megaevento deportivo sobre una economía local: el caso de los Juegos Mundiales 2013 Cali - Aguado, Luis F. (2017)
Purpose – A summary of the economic impact resulting from the celebration of a sporting mega-event in the city of Cali Colombia is carried out in this article. Design/methodology/approach – The impacts are estimated by means of the systematic effects produced by the activities of investment/expenditure of the identified agents and the consequent multiplying effects captured from an input-output model. Findings – The World Games represented a new income flow to the city of Cali of $101.036 million pesos (=US$53.4 mill.) and 9.598 jobs were created (=7711 full-time jobs). Additionally 2174 foreign tourists and 11250 national tourists were attracted to the city. Originality/value – The article contributes with innovative aspects methodologically speaking useful for future studies of economic impact in cities with low tourismlocated in developing countries.